Effects of planting spacing and refertilization on growth and nutrition of black spruce ( Picea mariana (Mill.) B.S.P.) planted on a minerotrophic peatland in Newfoundland, Canada - Wells, E. Doyle (Canadian Journal of Forest Research, 1994)
In 1973, a black spruce (Piceamariana (Mill.) B.S.P.) plantation was established in central Newfoundland on a minerotrophic, open peatland that had been ditched at 1.8 m spacings. The seedlings were planted at spacings of 1.2, 1.8, and 2.4 m and spot fertilized with a mixture of 71 g urea, 99 g ground rock phosphate, and 41 g potassium sulfate. In 1985, 12 years after establishment, concentrations of N (0.90%), P (0.10%), and K (0.28%) suggested that nutrient deficiencies were limiting growth. Consequently, P, P–K, and N–P–K were applied in the amounts of 60 kg/ha P, 100 kg/ha K, and 200 kg/ha N. Controls (no refertilization) were also included in the experiment, although these plots had been spot fertilized in 1973. Between 1985 and 1991, height growth, needle weight, and needle nutrients were not significantly different among planting-spacing treatments. Height growth was greatest in the P–K treatment, whereas needle weights were greatest in the N–P–K treatment in 1987. Uptake of N was significantly improved by application of P–K as well as by application of N–P–K. Concentrations of N, P, and K increased to levels of 2.43, 0.25, and 0.60%, respectively, following application of fertilizers containing those elements. However, by 1991, concentrations had decreased to 1.10, 0.14 and 0.43%, respectively. The effects of refertilization on uptake of Ca, Mg, and Cu were mainly nonsignificant.